Low transmission risk of 9 asymptomatic carriers tested positive for both SARS-CoV-2 nucleic acid and serum IgG. Issue 3 (September 2020) - Chen, Fenghua; Fu, Daan; Yang, Qianqian; Geng, Zhi; Xia, Jiahong; Wang, Zheng; Wang, Lin
Highlights: Asymptomatic carriers (RT-PCR+ and serum IgG+) are unable to transmit virus. Such a low transmission risk might be partly associated with high Ct values. A new pattern in SARS-CoV-2 infected patients might have emerged.